The role of law textbooks in the teaching and application of methods of legal interpretation in Poland (in historical and contemporary perspective) - Siemińska, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Celem artykułu jest wyjaśnienie roli wykładni prawa w Polsce w kontekście jej nauczania i stosowania, wynikające ze sposobu prezentacji wykładni prawa w podręcznikach prawa. Wyjaśnienie to oparte jest na następujących tezach: (1) współczesny sposób nauczania prawa w Polsce, w szczególności wykładni prawa oraz jej wpływu na stosowanie prawa, wynika z uwarunkowań historyczno- politycznych. (2) polskie podręczniki nauki prawa nie pokazują kontekstu politycznego i światopoglądowego prawa, co powoduje nieświadomość prawnopolitycznej roli wykładni prawa, (3) obecny stan polskiej nauki prawa, w szczególności- podręczników, przyczynia się do wzrostu znaczenia tzw. wykładni sędziowskiej i związanych z nią zagrożeń dla nauczania i stosowania prawa. Wyjaśnienie wskazanych tez pozwoli nie tylko na zrozumienie obecnej roli podręczników prawa w nauczaniu metody wykładni prawa cywilnego, ale także na pokazanie potencjalnego kierunku rozwoju teorii prawa. Istotnym jest zatem zwrócenie uwagi na szerszy kontekst, jakim jest sposób uprawiania nauki prawa w Polsce oraz jego wpływ na stosowanie i rozwój prawa, a także na świadomość prawną i poziom kultury prawnej.

The purpose of this article is to explain the role of legal interpretation in Poland in the context of its teaching and application, resulting from the way legal interpretation is presented in law textbooks. This explanation is based on the following theses: (1) the contemporary way in which law is taught in Poland, in particular law interpretation and its impact on the application of law, is due to historical and political conditions. (2) Polish law textbooks do not show the political and worldview context of the law, which results in an unawareness of the legal-political role of legal interpretation, (3) the current state of Polish law teaching, in particular textbooks, contributes to an increase in the importance of the so-called judicial interpretation and the related threats to the teaching and application of law. Clarification of the indicated theses will not only allow us to understand the current role of law textbooks in teaching the method of civil law interpretation, but also to show the potential direction of development of legal theory. It is therefore important to pay attention to the broader context, which is the way law teaching is practiced in Poland and its impact on the application and development of law, as well as on legal awareness and the level of legal culture.
Rola podręczników prawa w nauczeniu i stosowaniu metod interpretacji prawnej w polsce (w perspektywie historycznej i współczesnej)
The article is a significantly expanded, revised version of the paper “The role of Law Books in the Teaching and Application of Civil Law Interpretation Methods”, presented on 28 May 2021 on the framework of the Polish-German Seminar entitled “Legal handbooks – a European perspective”, organized by the University of SWPS in Warsaw, Augsburg Universität, UAM in Poznań, Universitá di Pisa and Aristotle University of Thessaloniki.
Keywords: wykładnia prawa; teoria prawa; podręczniki prawa; nauczanie wykładni prawa; metodologia prawa; legal interpretation; theory of law; legal textbooks; teaching of legal methods; legal methodology